Bankruptcy and Insolvency: An Exploration of Relevant Theories - Onakoya, Adegbemi Babatunde; Olotu, Ayooluwa Eunice (International Journal of Economics and Financial Issues, 2017)
The essence of the law on bankruptcy is to collect the debt of an entity and distribute such asset among the contending claimholders. It is, also meant to resolve the broad issues of business failure in the context of the imminent or indeed the actual collapse of the indebted entity. The objective of the study is to explore relevant theories guiding the procedure of distribution or entitlement in bankruptcy among a group of agents. The study employed exploratory research method via an extended literature review, to investigate the underlying principles guiding the allocation of a given amount of a perfectly divisible good among a group of agents. The results of this extended literature review indicate that the procedure of distribution or entitlement in bankruptcy is supported by five of the theories reviewed while only value based theory posits the absence of any cogent solution to the financial distress of the debtor. The knowledge of theories is not enough for business survival, the ability to predict the possible occurrence of business failures is necessary. Market based models including the stock market option valuation approach perform better than the earlier models which rely heavily on historical accounting figures. Keywords: Bankruptcy, Bankruptcy Theories, Exploratory Research, Genetic Programming Model JEL Classifications: G33, KII, K12